Overexpression of OsHox-6 Gene Enhanced Tiller Number in Rice But Induced Yield Penalty - Rahmawati, Syamsidah; Chairunnisa, Chairunnisa; Erdayani, Eva; Nugroho, Satya; Estiati, Amy (Annales Bogorienses, 2019)
OsHox-6, belongs to the transcription factor homeodomain leucine zipper (HD-Zip) protein sub-family I, has unknown function. This study was aimed to characterize the phenotypes of two homozygous transgenic rice lines (S29-62-2 and S.40.4-158-1) containing an extra copy of OsHox-6 gene under the control of a rice constitutive promoter, OsLEA3, and to evaluate their tolerance to water stress. A real-time quantitative PCR (qRT-PCR) showed that the transcript expression of OsHox-6 gene in the transgenic lines increased 5-10 folds under a normal irrigation and 10-20 folds after exposure to water stress conditions as compared to its wild type control. Transgenic plants overexpressing OsHox-6 exhibited phenotypic alteration at the normal irrigation by inducing tiller formation, suggesting a decrease in the apical dominance. Transgenic plants also showed significant enhancement in the total grain number, however, the number of empty grains also increased significantly (~16-22%). After imposed to the water stress, the number of empty grains in the transgenic lines was even higher (up to 83% in average). Furthermore, observations on the water loss rates, relative water contents and drought resistance indices (DRI) suggested that the overexpression of OsHox-6 did not significantly increase tolerance to water stress. Further research is required to reveal the detailed mechanisms of OsHox-6 in response to water and other abiotic stresses.